IMPLEMENTATION OF DATA ARCHIVE WAREHOUSE APPLICATION TO OPTIMIZE EMPLOYEE PERFORMANCE AT PALEMBANG PROBATION OFFICE - Hardi Dwi Saputra; Maulana; Chitra Imelda (Journal of Governance and Law Reform, 2026)
Digital transformation in public sector organizations has become a critical agenda for strengthening governance reform, yet its implementation often faces institutional, technological, and bureaucratic challenges. This study examines the implementation of the Gudang Arsip Data (GARDA) application as a digital governance instrument for optimizing employee performance at the Class I Correctional Center of Palembang. The research aims to analyze how digital archive transformation is implemented and identify factors influencing its effectiveness within a government institution. This study employs a socio-legal empirical research approach by combining normative analysis of digital governance regulations with qualitative investigation through interviews, observations, and document analysis. The findings indicate that GARDA improves administrative efficiency, document accessibility, and data management; however, its transformative impact remains constrained by limited infrastructure, insufficient technical support, employee adaptation challenges, and weak institutional integration. The study concludes that sustainable digital governance requires alignment between technology, legal frameworks, organizational capacity, and bureaucratic culture. This research contributes to digital governance studies by highlighting internal bureaucratic transformation as an essential dimension of public sector reform.